2020
DOI: 10.1186/s40644-020-0290-9
|View full text |Cite
|
Sign up to set email alerts
|

PSMA PET for primary lymph node staging of intermediate and high-risk prostate cancer: an expedited systematic review

Abstract: Background: PSMA PET is a promising method for primary lymph node staging in prostate cancer. However, recent systematic reviews have identified only a limited number of studies with histopathology as a reference test. Methods: A systematic search was performed in PubMed and the Cochrane Library. An expedited systematic review was performed where we identified diagnostic studies in prostate cancer where a preoperative PSMA PET for primary lymph node staging was compared to histopathology. The trials must have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
96
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 50 publications
2
96
0
1
Order By: Relevance
“…In the 90’s, the discovery of the prostate‐specific membrane antigen (PSMA), overexpressed in PCa, improved the clinical assessment of PCa by nuclear medicine imaging . Next to the presence in primary tumors, PSMA is expressed in metastases and primary lymph nodes, as well as in the recurrent disease . Hence, three PSMA‐targeting tracers have been clinically introduced for this purpose: [ 68 Ga]PSMA‐11, [ 18 F]PSMA‐1007 and [ 18 F]DCFPyL .…”
Section: Introductionmentioning
confidence: 99%
“…In the 90’s, the discovery of the prostate‐specific membrane antigen (PSMA), overexpressed in PCa, improved the clinical assessment of PCa by nuclear medicine imaging . Next to the presence in primary tumors, PSMA is expressed in metastases and primary lymph nodes, as well as in the recurrent disease . Hence, three PSMA‐targeting tracers have been clinically introduced for this purpose: [ 68 Ga]PSMA‐11, [ 18 F]PSMA‐1007 and [ 18 F]DCFPyL .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, PSMA PET/CT imaging was evaluated as a potential tool for staging primary prostate cancer in men prior to curative treatment [7]. Specificity rates of 84-100% were reported by earlier studies [8][9][10][11] and in a recent systematic review [12]. However, the sensitivity of PSMA PET/CT for the detection of lymph node metastases is moderate (33-91%), most likely due to the limitations in the spatial resolution to detect small (< 3 mm) lymph node tumour deposits in primary as well as recurrent prostate cancer [13].…”
Section: Introductionmentioning
confidence: 98%
“…Positron emission tomography (PET), combined with either computer tomography (CT) or magnetic resonance imaging (MRI), utilizing radiotracers that bind to prostate-speci c membrane antigen (PSMA) is an excellent diagnostic tool for prostate cancer imaging. In the past few years, PSMA-PET has evolved to become the leading advanced imaging modality in the Western world, especially for patients with early biochemical recurrence (EBR) [1,2]. In various studies, PSMA-PET/CT has shown better detection e cacy in EBR than MRI, CT, conventional imaging [3][4][5][6], or choline-labeled PET ligands [7].…”
Section: Introductionmentioning
confidence: 99%